New stiletto flies in the genus Anabarhynchus Macquart (Diptera: Therevidae) from Kangaroo Island, South Australia - Ferguson, D.j.; Glatz, R.v.; Yeates, D. K. (Zootaxa, 2019)
Anabarhynchus Macquart 1848 is a species-rich genus of stiletto flies (Diptera: Therevidae) belonging to the subfamily Therevinae, with over 113 species described from Australia. These flies are diverse and abundant in Australia’s eucalypt woodland and mallee habitats. Here we describe, diagnose and illustrate a further three new Anabarhynchus species in the genus as follows: A. aurantilateralis sp. nov. and A. halmaturinus sp. nov., and A. venabrunneis sp. nov., from Kangaroo Island. These new species bring the total number of described Australian species in the genus to 116, with 13 of these known to occur on Kangaroo Island.